Evaluasi dan Aplikasi Pupuk Organik Cair Larva Black Soldier Fly pada Pembibitan Awal bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Sylvia Madusari; Ratih Rahhutami; Ajeng Rizky Septiani (Politeknik Kelapa Sawit Citra Widya Edukasi, 2021)
Liquid organic fertilizer is a fertilizer made from the decomposition process of organic matter. Black soldier fly (BSF) larvae are used as organic fertilizer because they have a high protein content. This study aims to determine the content of BSF larvae liquid fertilizer (POCbsf) with pineapple and papaya extract as activators and the response to the growth of oil palm seedlings in early nurseries with BSF liquid organic fertilizer. This research was conducted in 2 stages, namely the stage of making POCbsf and the stage of testing POC on oil palm seedlings in early nurseries. This research was arranged in a non-factorial Completely Randomized Design (CRD). The experiments tested in this study were: P0 (without POC), P1: 0.1% POCbsf, P2: 0.5% POCbsf, P3: 1% POCbsf). Each study consisted of 4 treatments, with 3 replications, each replication consisting of 3 samples. The results showed that the amino acid content contained in POCbsf consisted of 17 types. The content of glutamic acid and aspartic acid in POCbsf with papaya extract activator was higher (0.14% and 0.08%) than POCbsf with pineapple extract activator (0.02% and 0.01%). Compared to the control, both POCbsf showed a positive increase in the growth of oil palm seedlings represented at 4 BST on plant height parameters (0.1% POCbsf A = 22.78 cm and 0.5% POCbsf B = 22.06 cm) and root length (0.5% POCbsf A = 15.9 cm; and 0.1% POCbsf B = 15.57 cm).